Analysis of hematological parameters in rheumatoid arthritis patients receiving biological therapy: contribution to prevention of avoidable hematological complications - Pereckova, Jana; Martiniakova, Silvia; Payer, Juraj; Falk, Martin; Killinger, Zdenko; Perecko, Tomas (EXCLI journal, 2022)
Administration of biological therapy (BT) in rheumatoid arthritis (RA) patients is often associated with hematological complications, which result in switching among therapies. Thus, there is an instant need for suitable screening parameters that will help to individualize the therapy and minimize the onset of adverse effects. We analyzed the hematological profile of 99 RA patients receiving TNFα (Adalimumab - ADA, Golimumab - GOL, Etanercept - ETA) or IL-6 receptor (Tocilizumab - TCZ) inhibitors in order to find possible indicators to improve personalization of RA therapy. BTs significantly affect the levels of observed hematological parameters. In contrast to TNF-α inhibitors, TCZ normalized almost all monitored hematological parameters to values of healthy donors. Only GOL from the TNF-α inhibitors studied, was able to normalize neutrophil counts, as well as platelet indicators. Importantly, effects on the blood parameters (e.g. lymphocytes or platelet count) differ even within the same therapeutic group (anti-TNFα). Variable effects of individual biological agents in RA treatment point to importance to evaluate the patient's hematological profile to improve the selection of suitable BT. It will help to personalize the administration of BT and prevent unnecessary switching from an effective therapy just because of provocation of avoidable hematological complications.
Keywords: TNFalpha; biological therapy; rheumatoid arthritis; IL-6; hematologic parameters